USING SHADOWING TECHNIQUE IN IMPROVING STUDENTS’ PRONUNCIATION ABILITY - Petalolo, Andi Alyfia; Mertosono, Sudarkam R.; Dewi, Anjar Kusuma (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the effectiveness of using Shadowing Technique in improving pronunciation abilty of grade seven students of SMP Negeri 3 Palu. The research employed a quasi-experimental design, involving an experimental group and a control group, with a total of 62 students from each group (VII G and VII I). The sample was chosen using a cluster random sampling technique. A Pronunciation test was used as the instrument of the research. The data were analyzed using a paired sample t-test with the assistance of SPSS 24. The results indicated that Shadowing Technique was effective in improving seven grade students pronunciation ability. This was supported by the significant difference in learning outcomes between the pre-test and the post-test, and evidenced by a paired sample t-test with a value significance (2-tailed) of 0.00 0.05.